2023
DOI: 10.3390/ijms241411849
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Immunotherapy: A Promising New Standard of Care

Abstract: Neoadjuvant immunotherapy has emerged as a promising approach in the treatment of various malignancies, with preclinical studies showing improved immune responses in the preoperative setting. FDA-approved neoadjuvant-immunotherapy-based approaches include triple-negative breast cancer and early non-small cell lung cancer on the basis of improvement in pathological response and event free survival. Nevertheless, current trials have only shown benefits in a fraction of patients. It is therefore crucial to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 109 publications
0
5
0
Order By: Relevance
“…The phase 3 NADINA trial is investigating the role of 2 cycles of ipilimumab (80 mg) and nivolumab (240 mg) before surgery [18] . Other neoadjuvant immunotherapy strategies, like intratumoral injections, are being investigated within ongoing or completed phase 3 trials (NeoDREAM NCT03567889, PIVOTAL NCT02938299) [19] .…”
Section: Underpowered Phase 2 Trialmentioning
confidence: 99%
“…The phase 3 NADINA trial is investigating the role of 2 cycles of ipilimumab (80 mg) and nivolumab (240 mg) before surgery [18] . Other neoadjuvant immunotherapy strategies, like intratumoral injections, are being investigated within ongoing or completed phase 3 trials (NeoDREAM NCT03567889, PIVOTAL NCT02938299) [19] .…”
Section: Underpowered Phase 2 Trialmentioning
confidence: 99%
“…Recently, the results of several randomized phase II and III trials of neoadjuvant and pre-operative ICI, combined with CT for resectable NSCLC, have been presented or published [ 27 ]. The theoretical advantage of a neoadjuvant approach stands in an enhance antitumor immune response as tumor antigens and lymph nodes are still in place [ 28 , 29 ].…”
Section: Management Of Stage III Nsclcmentioning
confidence: 99%
“…In the case of immune therapies, preclinical studies have shown that preoperative administration leads to increased survival. There are hypotheses suggesting that even a single dose of a PD-1 inhibitor could potentially stimulate the activity of cytotoxic lymphocytes [168]. Moreover, in the case of Pembrolizumab, randomized clinical trials have observed an increased efficiency of neoadjuvant administration.…”
Section: Treatment Of Cutaneous Melanomamentioning
confidence: 99%